Predicted and measured acute toxicity and developmental abnormalities in zebrafish embryos produced by exposure to individual aromatic acids. (August 2018) - Dogra, Yuktee; Scarlett, Alan G.; Rowe, Darren; Galloway, Tamara S.; Rowland, Steven J.
Abstract: Petroleum acids, often called 'Naphthenic Acids' (NA), enter the environment in complex mixtures from numerous sources. These include from Produced and Process-Affected waters discharged from some oil industry activities, and from the environmental weathering of spilled crude oil hydrocarbons. Here, we test the hypothesis that individual NA within the complex mixtures can induce developmental abnormalities in fish, by screening a range of individual acids, with known chemical structures. Sixteen aromatic NA were tested using a Thamnocephalus platyrus (beavertail fairyshrimp) assay, to establish acute toxicity. Toxicities ranged from 568 to 8 μM, with the methylbiphenyl acid, 4-( p -tolyl)benzoic acid, most toxic. Next, five of the most toxic monoacids and for comparison, a diacid, were assayed using Danio reri o (zebrafish) embryos to test for lethality and developmental abnormalities. The toxicities were also predicted using Admet predictor™ software. Exposure to the five monoacids produced deformities in zebrafish embryos in a dose-dependent manner. Thus, exposure to 4-( p -tolyl)benzoic acid produced abnormalities in >90% of the embryos at concentrations of <1 μM; exposure to dehydroabietic acid caused pericardial edema and stunted growth in 100% of the embryos at 6 μM and exposure to pyrene-1-carboxylic acid caused 80% of embryos to be affected at 3 μM. The findings of this preliminary study therefore suggest that some aromatic acids are targets for more detailed mechanistic studies of mode of action. The results should help to focus on those NA which may be important for monitoring in oil industry wastewaters and polluted environmental samples. Graphical abstract: Image 1 Highlights: Acute toxicity of 16 individual aromatic 'naphthenic' acids assayed (invertebrate). Lethality and developmental abnormalities of 6 individual acids assayed (fish). Toxicities modelled using commercially-available Admet predictor™ software. Significant relationship found between predicted and experimental fish LC50 s. Embryo abnormality EC50 s < 7 μM in 4 of 6 acids; 4- ( p -tolyl)benzoic acid most toxic.